Dynamic calibration of self-efficacy to cognitive load: the longitudinal mediation effect of state anxiety - Xiaolong Li; Mu Xia (BMC Psychology, 2024)
Abstract Background Previous research has shown that higher self-efficacy predicts lower cognitive load. Nevertheless, there is limited research exploring the dynamic calibration phenomenon of cognitive resources by self-efficacy during task execution through experimental methods. Methods This study elucidates the relationships and longitudinal mediating effects among self-efficacy, state anxiety, and cognitive load through two studies that employed convenience sampling. Study 1, which aims to provide a comprehensive theoretical understanding of the research question, is an interview study that examines the prevalence of fluctuations in self-efficacy among 22 university students through an in-depth interview. On the other hand, study 2 reveals further causal relationships through experimental methods. It adopts a 3 (repeated measures: first time, second time, third time) × 2 (conditions: feedback group, non-feedback group) mixed design by 86 participants, utilizing a false feedback paradigm to manipulate participants’ self-efficacy, with the task of the experiment being emotion recognition. Results The results demonstrate that, compared to the non-feedback group, false feedback can successfully manipulate the self-efficacy of the participants, and the data from the feedback group further reveals the multilevel mediating role of state anxiety in the process of self-efficacy influencing cognitive load. Conclusion In general, the findings from two studies suggest that the enhancement of college students’ self-efficacy during task execution can reduce their state anxiety, which in turn can further alleviate cognitive load.